Gender Issues in Participation - World Bank (Washington, DC, 2012)
The full participation of both men and women in policymaking, in economic and sectoral analysis, and in project design and management, may be impeded by cultural and legal constraints which limit women ' s participation and by women ' s relative lack of time and mobility due to their workload and multiple roles. If participatory development is to benefit from women ' s contributions, and meet the particular needs of women, a range of strategic and practical measures must be taken to overcome these barriers.